Attitude and Perception of Local Inhabitants towards Mangrove Ecosystems - Kaippilly, Dinesh; E.R., Chinchu; M.T., Geeji (Journal of Extension Education, 2018)
Conservation of the mangrove habitat is highly essential to protect the coastal regions and the livelihood of the local folk, mainly comprising fishermen community. Involvement of local inhabitants is the key factor for the success of all ecosystem conservation activities. In the present study, the attitude and perceptions of local people of Puduveypu area of Ernakulam District, Kerala towards the conservation of Mangrove ecosystem were examined. A total of 1966 respondents were surveyed. Among these, 52.3% of the villagers were positive and showed interests in the ecological importance of Mangrove ecosystems. A small group of people viewed that mangroves restrict their developmental activities and consider them as a menace. The study illustrates that it is important to inculcate a mangrove friendly lifestyle among these communities for better conservation of this ecosystem.